The creative thinking ability in anchored instructions (AI) learning reviewed from mathematical disposition - Soedjoko, Edy; Kurniati, Ika Tiara; Kurniasih, Ary Woro (Unnes Journal of Mathematics Education, 2019)
The purposes of this research were to test the learning process using Anchored Instructions (AI) model to reach the learning mastery and to describe the ability of creative thinking use Anchored Instructions (AI) reviewed from Mathematical disposition. This research was mix methods research with triangulation concurrent model. The population in this research was VII grade students of SMP N 3 Ungaran academic year 2017/2018. The sample was the students of VII-I class. Particularly, the subject of this research was the students of VII-I class who have high, medium, and low mathematical disposition category. This research used quantitative data to test the average of one group and the proportion of the other group. Further, the qualitative data were analyzed by Miles and Huberman model. In the process of the interview, there were two subjects in each mathematical disposition category. Eventually, the result of this research showed that the learning process by using Anchored Instructions (AI) model reached the learning mastery and described the ability of students' creative thinking with Anchored Instructions (AI) model reviewed from mathematical disposition. It was proven through the students with high mathematical disposition who had all of the aspects of mathematical disposition ability namely fluency, flexibility, and novelty. The students with medium mathematical disposition had fluency and flexibility aspect of mathematical disposition ability. The last, the students with low mathematical disposition only had one aspect of creative thinking ability that was fluency.